2018
DOI: 10.3390/app8112264
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Gold(I) and Gold(III) Using Multiwalled Carbon Nanotubes

Francisco Jose Alguacil

Abstract: Carbon nanotubes are materials that have been investigated for diverse applications including the adsorption of metals. However, scarce literature has described their behavior in the case of the adsorption of precious metals. Thus, this work reports the efficient adsorption of gold from cyanide or chloride media on multiwalled carbon nanotubes (MWCNTs). In a cyanide medium, gold was adsorbed from alkaline pH values decreasing the adsorption as the pH values were increased to more acidic values. In a chloride m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Alguacil [11] also characterized the possibility of applying MWCNTs as sorbents, but in this case, for gold(I) and gold(III) cations' adsorption from cyanide and chloride solutions. The reached data suggested that the recovery of the selected metal may be accomplished by subsequent elution with acidic thiourea solutions (for cyanide medium) or with aqua regia (for chloride solutions), with a further possibility of obtaining zero-valent gold nanoparticles.…”
Section: Adsorptionmentioning
confidence: 99%
“…Alguacil [11] also characterized the possibility of applying MWCNTs as sorbents, but in this case, for gold(I) and gold(III) cations' adsorption from cyanide and chloride solutions. The reached data suggested that the recovery of the selected metal may be accomplished by subsequent elution with acidic thiourea solutions (for cyanide medium) or with aqua regia (for chloride solutions), with a further possibility of obtaining zero-valent gold nanoparticles.…”
Section: Adsorptionmentioning
confidence: 99%
“…Among these residues, the materials generated from the electronic and communication industries are of importance [1,2], because they contained, among other valuable metals, gold. Thus, there is an interest, from worldwide researchers, to investigate methods for the recovery of this precious metal from these residues or, in general, gold-bearing wastes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Very often, the recovery of gold from these wastes is done by leaching of the waste with aqua regia, resulting in a leachate in which gold is present as AuCl4 -or HAuCl4 [5]. The recovery of this precious metal from the HCl solution can be done mainly by activated carbon [6], ion exchange resins [7][8][9][10], liquid-liquid extraction using conventional [11][12][13] and ionic liquid [14][15][16][17] extractants, different adsorbents [18][19][20][21][22] and as mentioned above by liquid membranes [23][24][25][26]; more recently, the use of carbon nanotubes have been also considered in the treatment of dilute Au(III)-bearing HCl solutions [27][28][29].…”
Section: Introductionmentioning
confidence: 99%